411. Application of a SARS-CoV-2-specific serologic assay for translational research and surveillance. (31st December 2020) - Sherman, Amy C; Smith, Teresa C; Espinoza, Daniel; Zhu, Yerun; Howard-Anderson, Jessica; Taibl, Kaitlin R; Fairley, Jessica K; Wu, Henry M; Edupuganti, Sri; Rouphael, Nadine; Rouphael, Nadine; Rodriguez-Morales, Alfonso J; et al.
Abstract: Background: Sensitive and specific SARS-CoV-2 antibody diagnostics are urgently needed to estimate the seroprevalence of SARS-CoV-2 infection in both the general population and special risk groups. Moreover, validated serologic assays are critical to understanding immunity to SARS-CoV-2 infection over time and identifying correlates of protection. Methods: An enzyme-linked immunosorbent assay (ELISA) protocol to detect antibodies (IgG) that bind the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein was validated and ROC curve analysis performed by testing a large panel of pre-pandemic sera (n=162) and convalescent sera from RT-PCR-confirmed COVID-19 cases (n=60). We then applied this test in two cohorts: 1) Healthcare personnel (HCP) that were enrolled in a longitudinal surveillance cohort just after peak local transmission and 2) Mildly ill patients being tested for SARS-CoV-2 infection by RT-PCR from NP swabs in an ambulatory testing clinic. Demographics of mildly symptomatic patients tested for SARS-CoV-2 with RT-PCR Results: ROC curve analysis yielded an AUC of 0.9953, with a sensitivity and specificity at 91.67% and 99.38% at the optimal OD normalization threshold of 0.20. In 240 HCP surveilled at enrollment, 5.83% had positive IgG results. Of 19 symptomatic patients who presented to the ambulatory clinic, 5/19 had a positive PCR. In convalescence (13–74 days post symptom onset), 3 of those 5 were positive for IgG. Validation of the SARS-CoV-2 RBD ELISA ROC Curve Analysis Conclusion: We demonstrated high sensitivity and specificity of the SARS-CoV-2 RBD ELISA. This simple assay is an efficient way to track seroconversion and duration of antibody responses to SARS-CoV-2 for different populations, particularly since RBD-binding antibodies have been shown to correlate with neutralization activity and may be useful to determine protective immunity following natural infection or vaccination. Ongoing work will assess variation in magnitude, character and duration of antibody responses in key populations and seek to maximize deployability of large-scale SARS-CoV-2 serology. Disclosures: Jessica Howard-Anderson, MD, MSc, Antibacterial Resistance Leadership Group (ARLG ) (Other Financial or Material Support, The ARLG fellowship provides salary support for ID fellowship and mentored research training) Nadine Rouphael, MD, Lilly (Grant/Research Support)Merck (Grant/Research Support)Pfizer (Grant/Research Support)Quidel (Grant/Research Support)Sanofi Pasteur (Grant/Research Support)